Facile fabrication of SnSe nanorods embedded in GO nanosheet for robust oxygen evolution reaction. Issue 1 (31st December 2023) - Manzoor, Sumaira; Alsaiari, Norah Salem; Katubi, Khadijah Mohammedsaleh; Nisa, Mehar Un; Abid, Abdul Ghafoor; Chughtai, Adeel Hussain; Abdullah, Muhammad; Aman, Salma; Al-Buriahi, M. S.; Ashiq, Muhammad Naeem
Abstract : Excessive use of fossil fuels has caused their rapid depletion, resulting in a growing energy crisis as well as many environmental concerns, and prompting the development of the sustainable energy conversion system. In this study, we report GO based SnSe nanomaterial incorporated via the hydrothermal route engaging OER activity. The morphological, structural and textual effects of the material have been measured with scanning electron microscopy (SEM), X-ray diffraction (XRD) and Brunauer Emmett Teller (BET). Furthermore, the kinetic process, active sites, conductivity and stability of the electrode medium of GO, SnSe and GO/SnSe were estimated with electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV), electrochemical active surface area (ECSA) and chronoamperometry under 1.0 M KOH with Ni foam as a conductive substrate. Its electrochemical results depicted the following: the GO based SnSe nanocomposite displayed lesser overpotential around 336 mV to reach a current density around 10 mA cm −2 and Tafel slope of 36 mV dec −1 . Cyclic stability and chronoamperometry analysis of GO/SnSe nanocomposite show stability over 35 h. The exceptional electrochemical properties of the GO/SnSe nanocomposite differentiate it as a good material for use in electrical and in many other fields in future.